Ethical issues of xenotransplantation in the aspect of religious views - R. A. Sharifova; A. Kh. S. Al Breizat; M. M. Kaabak; U. V. Maslikova; B. I. Yaremin (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2022)
Transplantation allows us to confidently save the lives of previously doomed patients. Unfortunately, this colossal achievement of human progress has a problematic side – the shortage of donor organs. The use of animal organs could solve it. Currently, the issues of xenotransplantation have become relevant again after the experimental xenotransplantation of the kidney of a genetically modified pig in 2021, and the xenotransplantation of the heart in 2022. This practice raises a number of ethical questions. Is it ethical to put humanity at risk by saving one person? Is it ethical to limit the civil rights of a xeno-recipient? Will xenotransplantation create another reason for discrimination? Can the creation of xenochimeras be considered an unacceptable interference in the Divine plan from a religious point of view? Is it ethical to use higher animals for xenotransplantation? Will an increase in the number of xenotransplants create a risk of the identity of the human race? Will xenotransplantation create new questions about equitable organ allocation? The sources of scholars of theologians related to the main Abrahamic religions on this topic are analyzed. Consideration of theological approaches to the new ethical problems presented by xenotransplantation does not allow us to find a unanimity of opinion. However, as this new branch of medical science makes concrete clinical progress, the attitude of society, religious leaders and ordinary believers towards it will improve. From an individual point of view, Judaism does not object to xenotransplantation to prolong and save human life, even in the case of non-kosher animals with genetic modifications. The preservation of life outweighs other values almost without exception. Xenotransplantation, even from a pig, is hailed as a life-sustaining medical intervention from a Jewish ethical perspective by most authors. In Christianity, the motivation is to try to follow the example of Jesus Christ in bringing healing to all those in need. While physiological healing is important, the ultimate goal is the overall well-being of the individual, which requires spiritual, mental, and social well-being in addition to physical health. The most correct generalization about Islamic bioethical views on xenotransplantation would be that, given the state of science, the final ethical and legal definition remains ambiguous, but in general, xenotransplantation as a means of saving human life may be acceptable.